Personal Character and Firm Performance. The Economic Implications of Having Fraudulent Board Members - Amir, Eli
Unique proprietary data on Swedish board members reveal that a non-trivial proportion of board members in Swedish listed firms have been convicted of serious crimes. Analyzing the data shows that board members with personal fraudulent behavior are more likely to be males than females. We also find that the greater the proportion of fraudulent board members, the lower is the profitability and the higher are the earnings (and cash flows) volatility of the firm. However, the negative effect of fraudulent behavior on profitability is mitigated when fraudulent board members have a larger stake in the firm’s equity. Finally, we find that the earnings of firms with more fraudulent board members are lower and less value-relevant. Given the strong legal enforcement in Sweden, our results raise serious concerns about the effects of board members’ personal fraudulent behavior on firm performance and risk-taking in other countries, particularly the United States and the United Kingdom.Fraudulent behavior; Fraud; Crimes; Convicted board members; Corporate governance; Profitability; Earnings volatility